Use of Nab-Paclitaxel Plus Gemcitabine Followed by Hypofractionated Tomotherapy With Simultaneous Integrated Boost in Patients With Locally Advanced Pancreatic Cancer - Shi, Zhan; Yang, Ju; Kong, Weiwei; Qiu, Xin; Lu, Changchang; Liu, Juan; Liu, Baorui; Du, Juan (Frontiers in Oncology, 2022)
Background and Purpose: A phase 2 study LAPACT indicated nab-paclitaxel plus gemcitabine (AG) improved outcomes of patients with locally advanced pancreatic cancer (LAPC). Conventional radiotherapy failed to show benefit, indicating high dose to volume with high risk of recurrence is needed. The high dose can be delivered through hypofractionated tomotherapy with simultaneous integrated boost (SIB). However, there is a lack of such prospective trials and more data are needed to validate the role of AG plus hypofractionated tomotherapy with SIB in patients with LAPC. Materials and Methods: Patients with LAPC receiving AG plus tomotherapy at Nanjing Drum Tower Hospital between 2018 and 2021 were retrospectively analyzed. The treatment was scheduled as follows: nab-paclitaxel 125mg/m2 plus gemcitabine 1,000mg/m2 on days 1 and 8 every three weeks for at least two cycles, followed by hypofractioned tomotherapy with SIB (high dose field: 50Gy/10 fractions, the remainder: 30Gy/10 fractions). Then patients were given AG until intolerance or disease progression. Results: Overall, 22 patients completing the chemoradiotherapy were included. The median follow-up was 15.2 months. After the chemoradiotherapy, 5 patients achieved a partial response (PR), 15 had a stable disease (SD), and another 2 patients were with progressive disease (PD). The median progression-free survival (PFS) and overall survival (OS) were 12.8 months (95% confidence interval [CI] 4.3-21.3 months) and 16.3 months (95%CI 10.9-21.6 months), respectively. The optimal carbohydrate antigen (CA) 19-9 response and chemotherapy cycles≥6 were correlated with favorable PFS and OS. The most common recurrent pattern was peritoneal dissemination (22.7%) and the locoregional recurrence rate was relatively low (4.5%). Treatments were well-tolerated. The most common grade≥3 adverse event was thrombocytopenia (13.6%). Conclusion: This study demonstrated the feasibility of AG followed by hypofractioned tomotherapy with SIB in patients with LAPC. The hypofractionated tomotherapy with SIB was safe and showed high local control rate. Further study with a larger population to validate our data is underway.